Roots and wings of ignatian spirituality in Gregorianum - Michael, Pavulraj (Gregorianum, 2019)
The centenary of Gregorianum should be an appropriate moment to rekindle the glorious intellectual tradition of Gregorian University, Rome. It’s time to rethink, reflect, reminisce and reassure the generations to come that the true spirit of Gregorianum would be assiduously preserved and promoted. The professors of Gregorian University in general and the professors of the Institute of Spirituality in particular have richly contributed to the growth of this magazine Gregorianum in the specialized areas like Theology, Philosophy, Canon Law, History of the Church, Spirituality, Psychology, Missiology and so on. When it comes to Spirituality and Spiritual Theology, the authors of Gregorianum for the last 100 years have contributed considerably onthe different aspects of Spirituality by writing on different themes like Spirituality and Theology, Spirituality and Mariology, Spirituality and Ecclesiology, Spirituality in the lives of Saints, Spirituality and Religion, Spirituality and Interreligious Dialogue. In all these areas the authors opened new avenues of interdisciplinary and transdisciplinary research by bringing forth newness in Spirituality and Spiritual Theology. In this article, as we are looking back to the 100 years of Gregorianum, we shall concentrate on the specific contribution of the authors in the area of Ignatian Spirituality. In this paper, by rereading and analyzing Gregorianum, it is interesting to see how Gregorianum helped the scholars of Spirituality in general and Ignatian Spirituality in particular to read the signs of times and respond to them adequately and intelligently in the light of Ignatian Spirituality. As we celebrate the Centenary Year of “Invisible Goodness” that we received for our Journal Gregorianum let us wish for another century to celebrate with dream, diligence, desire and vision.